Screening for modulators of cisplatin sensitivity: Unbiased screens reveal common themes - Nijwening, Jeroen H.; Kuiken, Hendrik J.; Beijersbergen, Roderick L. (Cell cycle (Georgetown, Tex.), 2011)
Cisplatin is a widely used chemotherapeutic agent to treat a variety of solid tumors. The cytotoxic mode of action of cisplatin is mediated by inducing conformational changes in DNA including intra- and inter-strand crosslink adducts. Recognition of these adducts results in the activation of the DNA damage response resulting in cell cycle arrest, repair, and potentially, apoptosis. Despite the clinical efficacy of cisplatin, many tumors are either intrinsically resistant or acquire resistance during treatment. The identification of cisplatin drug response modulators can help us understand these resistance mechanisms, provide biomarkers for treatment strategies, or provide drug targets for combination therapy. Here we discuss functional genetic screens, including one performed by us, set up to identify genes whose inhibition results in increased sensitivity to cisplatin. In summary, the validated genes identified in these screens mainly operate in DNA damage response including nucleotide excision repair, translesion synthesis, and homologous recombination.